DNA Barcode of Seven Indonesian Hornbills Species (Aves: Bucerotidae) Based on Mitochondrial DNA Cytochrome Oxidase Subunit I - Jarulis Jarulis; Dedy Duryadi Solihin; Ani Mardiastuti; Lilik Budi Prasetyo (HAYATI Journal of Biosciences, 2018)
DNA barcoding based on mitochondrial DNA COI gene is very useful in identifying of Indonesian hornbill. We sequenced the DNA barcode of seven hornbill species using the mitochondrial DNA COI gene to explore their genetic variation, identity, distance, and phylogenetic. Thirty-one blood samples from seven hornbill species were isolated and analyzed. Slight variation was observed within the nucleotide of the hornbill species. In contrary, fairly significant difference was shown within the genus and family level. COI gene sequences generated from this study, showed unmatched result with BoLD System database. These seven Indonesian hornbill species were then divided into two groups, namely Group I consisting of Aceros cassidix, Rhyticeros plicatus, R. undulatus, Buceros rhinoceros, and B. bicornis, while Group II occupied by Anthracoceros albirostris and A. malayanus; both groups with genetic distance 5.90%. Overall in-group had 9.40% distances to the hornbill used as the out group. COI sequence gene from these seven hornbill species are novel for identifying Indonesian hornbills. We encourage its use as quick species identification, applied to prevent illegal poaching conservation management.